Contact networks and regional milieux in rural areas.: Contribution to the concept of the regional milieu and emipirical experiences from Baden-Württemberg/Germany - Lenz, Barbara; Kulinat, Klaus (ERDKUNDE, 1997)
The milieu model is one of a series of recent theoretical models aimed at understanding the importance of regional relationships in the process of economic development so as to provide a starting point for regional policy discussion. Interaction between firms, institutions and the private sphere results in the emergence of a positive milieu in which economic development can be started and sustained, above all through synergy effects and innovative activity. Within the theoretical discussion the contact fields outside the directly business-related spheres have still received comparatively little attention and few empirical studies exist which differentiate with respect to actors and contact fields. Therefore the theoretical discussion will be extended here to the area of the actors’ contacts and networks. This seems to be both sensible and necessary in an extremely actor-centred model which initially had nothing to do with regional relations. n fact almost the only task of the network relationships outside the firms-to-firms contact field is to channel information and communication between actors in the different groups; but thereby additional synergy effects can be created which could not have come about if the actors had confined their interactions to their own social groups. So it can be assumed that an extra potential emerges consisting of contact possibilities based on personal acquaintance, which might of special interest for economic development in rural areas. The empirical results are based on a survey of 454 firms in six rural areas of Baden-Württemberg/Germany and focus on the problem of synergy effects in particular between the economic and private sphere. Considerable variances of contact quality and contact intensity within the different contact fields can be demonstrated. On the other hand, it was not possible to work out any typology which could confirm the model of the regional milieu. Nevertheless it would be certainly wrong to conclude that raising doubts about the milieu model implies that there is no point in making political and institutional efforts to establish linkages among regional business activities. The empirical results have clearly shown that the firms themselves see these as necessary.